Modeling photomolecular effect using generalized boundary conditions for Maxwell equations - Chen, Gang (Communications physics, 2024)
We recently demonstrated via experiments in hydrogels and at a single air-water interface the photomolecular effect: photons directly cleaving off water molecular clusters in the visible spectrum where bulk water has negligible absorption. To model single interface experiments, here we re-derive generalized boundary conditions for Maxwell equations by assuming a transition region of the electromagnetic fields across the interface, leading naturally to the Feibelman parameters used before to describe surface photoelectric and surface plasmon effects on metals. This generalization leads to modifications of the Fresnel coefficients and an expression for the surface absorptance that can reasonably explain trends in our single-interface experimental data on the angle and polarization dependence of the beam deflection. Our work provides further support for the existence of the photomolecular effect, suggests that surface absorption should exist in many materials, and lays a foundation for assessing the impacts of such surface absorption based on the Maxwell equations. The newly discovered photomolecular effect reveals that photons can evaporate water clusters in the visible spectrum where bulk water absorbs little. This work generalizes boundary conditions for Maxwell’s equations with Feibelman parameters and presents modified Fresnel coefficients and interfacial absorptance predicting trends consistent with experiments.